The pharmacokinetics of hexylresorcinol-containing lozenges and their antimicrobial efficacy against oral and respiratory microorganisms - Priyanka Sharma; Charlotte Richards; Jennifer Y. M. Adams; Kirsten Bentley; Aamir Razzak; Nicholas Claydon; Thomas Hallett; Graca Coutinho; Anuradha Kulasekaran; Lydia C. Powell; Richard J. Stanton; Elaine L. Ferguson; et al. (Journal of Oral Microbiology, 2025)
Background Hexylresorcinol (HR) lozenges provide symptomatic relief for sore throats. Despite its recognised anaesthetic and antiseptic properties, evidence of HR bactericidal activity in these formulations is limited, being only recently described in planktonic bacteria. We defined antimicrobial/antiviral activity in planktonic and biofilm models and characterised the pharmacokinetics of HR release from lozenges.Methods Antimicrobial activity (purified or released from lozenges) was determined against oropharyngeal pathogens using minimum inhibitory concentration (MIC) and Log10 reduction assays. Antiviral activity was determined by suspension test (EN14476). Antibiofilm effects employed minimum biofilm eradication concentration assays and confocal laser scanning microscopy. HR release from lozenges was studied in vitro and in vivo using HPLC.Results HR exhibited MICs ≤ 16 µg/mL against 19/25 strains including: Streptococcus, Staphylococcus and Candida spp. Marked bactericidal activity (>3log10; >99.9% reduction) occurred within 10 minutes. Significant anti-biofilm activity was evident in streptococcal and candidal biofilms (p < 0.05). Log10 reduction in virucidal infectivity of HR in lozenges ranged from 1-log10 to 3.5-log10. In vivo, HR exhibited rapid release (within 1 minute) from lozenges into saliva.Conclusion Rapid release and antimicrobial activity of HR against oropharyngeal pathogens was evident, occurring at concentrations ≥ 2-fold lower than present in saliva, highlighting the potential application of HR in the treatment of oropharyngeal infections.